n → ∞ lim n n ! n n ( 2 n ) !
If the value of the limit above equals to A × e B for integers A and B , find the value of A × B .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The logarithm of the given expression a n = n . . . is ln ( a n ) = ∑ k = 1 n ln ( 1 + n k ) n 1 , a Riemann sum of ln ( x ) from 1 to 2. Thus lim n → ∞ ln ( a n ) = ∫ 1 2 ln ( x ) d x = 2 ln ( 2 ) − 1 and lim n → ∞ a n = e 2 ln ( 2 ) − 1 = e 4
Nice observation of the Riemann sum interpretation.
that is a very useful solution
Stolz Lemma makes this immediate.
I'm using approximation for central binomial coefficient n ! n n ( 2 n ) ! = ( n ! ) 2 n n ( 2 n ) ! n ! = 2 π n 4 n ⋅ e n 2 π n n n = e n 4 n ⋅ n n Gives us limit lim n → ∞ ( n ! n n ( 2 n ) ! ) n 1 = e 4
No, that's not correct, the equal sign (highlighted in red) is not correct:
n ! n n ( 2 n ) ! = ( n ! ) 2 n n ( 2 n ) ! n ! = 2 π n 4 n ⋅ e n 2 π n n n = e n 4 n ⋅ n n
Do you know how to fix this? Does changing it to an approximation sign fix it? Why or why not?
Problem Loading...
Note Loading...
Set Loading...
Use Stirling's Approximation to re-express this as follows
n n ! n n ( 2 n ) ! = n 2 π n ( e n ) n n n 2 π 2 n ( e 2 n ) 2 n = ( 2 ) n 1 ( e 4 )
As n → ∞ , this becomes
( 2 ) n 1 ( e 4 ) = ( e 4 ) = 1 . 4 7 1 5 6 8 7 6 4 . . .